2020
DOI: 10.21037/apm-20-397
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial and red blood cell microparticles with acute myocardial infarction in Chinese: a retrospective study

Abstract: Background: Mounting evidence suggests that endothelial cell-derived microparticles (EMPs) and red blood cell-derived microparticles (RMPs), which have procoagulant and vasoconstriction effects, are involved in the development of vascular acute cardiovascular events. The aim of this study was to analyze the circulating levels of EMPs and RMPs in patients with acute myocardial infarction (AMI), and to explore the correlations between EMPs and RMPs and the severity of coronary artery disease.Methods: Plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition, in malignant diseases, there is a link between TF+MPs and the recurrence of VTE [ 54 ]. Furthermore, RMPs and EMPs have been regarded as putative agents in the development of coronary heart disease and vascular events, e.g., acute myocardial infarction, whereas GMPs and other WBCs-derived MPs interact with immune cells and enhance the production of pro-inflammatory cytokines, participating in the pathogenesis and evolution of cardiovascular and allergic disorders, infections, pre-eclampsia or cancer [ 55 , 56 ]. Overall, we may hypothesize that MPs and CECs can be employed as diagnostic tools in MPNs, to differentiate between MPNs subtypes and secondary causes of polycythemia, thrombocytosis or myelofibrosis, and also to predict the occurrence of vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in malignant diseases, there is a link between TF+MPs and the recurrence of VTE [ 54 ]. Furthermore, RMPs and EMPs have been regarded as putative agents in the development of coronary heart disease and vascular events, e.g., acute myocardial infarction, whereas GMPs and other WBCs-derived MPs interact with immune cells and enhance the production of pro-inflammatory cytokines, participating in the pathogenesis and evolution of cardiovascular and allergic disorders, infections, pre-eclampsia or cancer [ 55 , 56 ]. Overall, we may hypothesize that MPs and CECs can be employed as diagnostic tools in MPNs, to differentiate between MPNs subtypes and secondary causes of polycythemia, thrombocytosis or myelofibrosis, and also to predict the occurrence of vascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the clinical differences between AMI patients and SCAD patients, which are mainly related to the pathophysiology of the acute and stable states, SCAD patients were selected as the control group. Our team’s previous research found that MPs play extremely important roles in the occurrence and development of CVD [ 14 ]. Therefore, in this study, a proteomic analysis was performed of the MPs from the coronary blood of patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Zacharia et al [ 13 ] found that MPs increase inflammation and thrombosis in acute coronary syndrome (ACS) patients, and their concentration is positively correlated with the degree of coronary artery stenosis in ACS patients. A previous study revealed elevated levels of EMPs in AMI patients, and EMP levels are associated with the degree of coronary artery disease and prognostic risk [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al revealed increased levels of RBC EVs in Chinese individuals with acute myocardial infarction compared to those with non-coronary artery disease. However, no significant difference in RBC EV levels was observed in Thrombolysis in Myocardial Infarction (TIMI) risk stratification [69]. Giannopoulos et al reported that STEMI patients treated with primary percutaneous coronary intervention (PCI) had increased levels of RBC EVs (twice that of healthy volunteers).…”
Section: Cardiovascular Disease (Cvd)mentioning
confidence: 99%